Business Ethics An Economically Informed Perspective - Lütge, Christoph (Oxford University Press, 2021)
Business ethics continues to gain importance in the curricula of business studies courses. This book provides a comprehensive overview of both the essential concepts of business ethics related to the economy as a whole, and the more narrowly understood corporate ethics related to the individual company. In contrast to other works on the same topic, special emphasis is placed on a coherent theoretical foundation that puts tools of economic analysis, including behavioral economics, at the center. In particular, the importance of both empirical research and dilemma structures for business ethics receives special attention. The largest chapter of the book is devoted to corporate ethics and provides students and academics with guidance in the theoretical classification of the variety of concepts that often coexist in the debate. Abstract concepts are illustrated with the help of practice boxes.